2013
DOI: 10.1186/1746-4811-9-34
|View full text |Cite
|
Sign up to set email alerts
|

A valid strategy for precise identifications of transcription factor binding sites in combinatorial regulation using bioinformatic and experimental approaches

Abstract: BackgroundTranscription factor (TF) binding sites (cis element) play a central role in gene regulation, and eukaryotic organisms frequently adapt a combinatorial regulation to render sophisticated local gene expression patterns. Knowing the precise cis element on a distal promoter is a prerequisite for studying a typical transcription process; however, identifications of cis elements have lagged behind those of their associated trans acting TFs due to technical difficulties. Consequently, gene regulations via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Except for the missing values, genes expressed in at least one tissue all had a complete motif that was suitably located ( Figures 5B,C ). As expected, the most conserved motif of clade A genes embraced adjacent MYB and bHLH binding sites, two transcription factors of the MBW transcriptional regulatory complex, which have been experimentally verified in several species (Wang et al, 2013; Zhu et al, 2015). We then analyzed the conserved motif in each sub-clade.…”
Section: Resultssupporting
confidence: 66%
“…Except for the missing values, genes expressed in at least one tissue all had a complete motif that was suitably located ( Figures 5B,C ). As expected, the most conserved motif of clade A genes embraced adjacent MYB and bHLH binding sites, two transcription factors of the MBW transcriptional regulatory complex, which have been experimentally verified in several species (Wang et al, 2013; Zhu et al, 2015). We then analyzed the conserved motif in each sub-clade.…”
Section: Resultssupporting
confidence: 66%
“…MYB118 encodes an R2R3-type MYB TF harboring two adjacent R repeats, which is a common feature of plant MYBs. Although many R2R3-MYB TFs recognize AC elements (DNA motifs enriched in adenosine and cytosine residues), the range of R2R3-MYB binding sites remains poorly defined in planta (Prouse and Campbell, 2012;Wang et al, 2013). Our observations suggest that the TAACGG element is part of the in vivo MYB118 binding site.…”
Section: Myb118 Antagonistically Regulates Distinct Gene Subcircuitsmentioning
confidence: 82%
“…In plants the MYB transcription factors contains R2 and R3 domains and the binding sequence varies from four to 14 nucleotides. 12 In Arabidopsis it has been shown that the β-glucoronidase gene driven by AtMYB2 promoter was inducible by osmotic stresses. 13 The upstream analysis of SamDC promoter showed the presence of W-Box elements and MYB regulatory cis elements (TAACTG).…”
Section: Wrky and Myb Cis Regulatory Elementsmentioning
confidence: 99%